Correlational study on Obesity Indicators and Blood Pressure in Productive Age Group - Umara, Annisaa Fitrah; Winahyu, Karina Megasari; Yoyoh, Imas (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: Hypertension causes various health problems worldwide, including in Indonesia. High blood pressure that occurs in productive age and unmanaged properly can increase various risks of disease which amya lead to health burden nationally and globally.  . Currently, the lifestyle of the productive age group contributes to obesity and hypertension, amplifying the risk factors for increased Cardiovascular Disease (CVD).Objective: This study aimed to analyze the relationship between obesity indicators and blood pressure in the productive age group.Methods:  A survey was conducted at a total of  150 respondents aged 25-64 years who had jobs, had no impaired physical mobility, and had no pregnancy. . Measurements included Systolic and Diastolic Blood Pressure, Body Mass Index (BMI), waist circumference, Waist to Height Ratio (WHtR), and Waist to Hip Ratio (WHR). The data was analyzed using the Pearson correlation test.Results: The majority of the respondents were male, aged 30-39 and 40-49 years, normal range of BMI and waist circumference, but WHR and WHtR on high risk. More than half of the total respondents in the productive age group had blood pressure in the normal range. There was a strongest positive correlation between waist circumference with SBP and BMI with DBP.Conclusion: Individuals in the productive age group with higher waist circumference and BMI are more prone to elevated blood pressure. Regular health screening and lifestyle change intervention are crucial to prevent hypertension in the productive age group.